Evaluasi kebijakan pro masyarakat miskin (studi kasus program raskin di Kabupaten Manokwari) - Yuyun Puji Rahayu; Danny E. Waimbo; Marco Kabiay (Jurnal Ekonomi dan Bisnis, 2019)
The government has sought to stabilize the lives of the poor by implementing programs directly perceived by the poor, one of which is the subsidized rice program for poor households (Raskin). There is a need to do an evaluation of how the Raskin community responds to the implementation of the Raskin program, whether the rules (mechanisms) in Raskin distribution are accurate, and what constraints are faced in the implementation of Raskin Program in Manokwari Timur Village. The research method is descriptive percentage by taking as many as 88 Raskin recipients (RTS-PM) as sample. The results showed that the satisfaction of Raskin recipients was included as standard, the effectiveness of the Raskin Program (Accuracy of the rules) included in the poor category, and the biggest Raskin program obstacle in Manokwari Timur Village was the absence of socialization of the Raskin program. The distribution of Raskin is sometimes inaccurate in terms of target, time, quantity and price.